The Effect of 8-Week Core Training on Running Based Anaerobic Sprint Ability of Footballers - Mehmet Koçak, Hamza Küçük, Faruk Albay, Dila Şeyda Taşdemir (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this study was to examine the effects of 8-week core strength training on the repetitive sprinting ability, anaerobic power, body mass and fatigue indexes of football players. Methods: 15 male football players who play football regularly participated in the study. A core strength training program was applied to the research group using BOSU (Theraband, USA) elastic band (Theraband, USA). Before and after the study, the participants were analyzed with Tanita BC418 and their Body Mass Indexes (BMI) were taken. The height of the participants was measured with a stadiometer with a sensitivity of 0.01 cm. The data were analyzed using the SPSS 22 package program. Paired T Test was used for pre-test and post-test comparison between the two groups as the data showed normal distribution. Results: A high level of significant difference was found in the RAST and BMI values of the participants before and after the training when the averages were compared (p<0.05). A high level of significant difference was found in the Maximal Power and Fatigue Index values of the study participants when the pre- and post-training averages were compared (p<0.05). Conclusion: As a result, 8-week core exercises with Bosu and Tera tape improved the ability of repetitive sprinting, which is one of the important features of football players. As a result of the study, it can be said that the BMI level of the football players increases with the muscle mass developed as a result of core training.